غیر مسلم ممالک میں نکاح اور سیروگیسی سے متعلق مسائل و احکام:ایک تجزیاتی مطالعہ: A Study of the Issues and Rulings related to Marriage and Surrogacy in Non-Muslim Countries (Al-Qamar, 2021)
Marriage (Nikah) is a contract between a man and women which allows them to have an intimate. In surrogacy there is no legal wed lock, and the surrogate mother just consents to carry a pregnancy for intended parent(s).Islam encourages one to marry, it does not matter how engrossed one becomes chasing their dreams i.e. education, work and trade, it is secondary as getting married is cited as completing half of your faith. Such a partner should possess inner and outer beauty as well as a good education and proper upbringing, along with good manners however this is not a prerequisite. Islam teaches one should look to favour inner beauty as outer beauty fades. One must try to avoid a partner who is infertile or has bad character. Wealth and lust should be completely overlooked. In this article we are not just discussing the Islamic laws regarding marriage, but also discussing an important topic in today's world, surrogacy, in the light of Quran, Hadith and Highly Ranked Scholars.
Keywords: Non-Muslims Countries; Marriage; Surrogacy